2014
DOI: 10.1016/b978-0-12-420118-7.00006-8
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Guanfacine as a Therapeutic Agent to Address Stress-Related Pathophysiology in Cocaine-Dependent Individuals

Abstract: The pathophysiology of cocaine addiction is linked to changes within neural systems and brain regions that are critical mediators of stress system sensitivity as well as behavioral processes associated with the regulation of adaptive goal-directed behavior. This is characterized by the up-regulation of core adrenergic and corticotrophin releasing factor (CRF) mechanisms which sub-serve negative affect and anxiety and impinge upon intracellular pathways in the prefrontal cortex underlying cognitive regulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 294 publications
(386 reference statements)
1
17
0
Order By: Relevance
“…In line with our findings, a recent review highlights the potential of guanfacine as a therapeutic agent to attenuate stress‐induced and cue‐induced craving in cocaine‐dependent individuals (Fox & Sinha ). The authors further propose that guanfacine may be an effective medication to reduce craving and relapse vulnerability in other forms of addiction as well, because of its ability to improve cognitive and emotional control over drug‐seeking behavior (Fox & Sinha ).…”
Section: Discussionsupporting
confidence: 87%
“…In line with our findings, a recent review highlights the potential of guanfacine as a therapeutic agent to attenuate stress‐induced and cue‐induced craving in cocaine‐dependent individuals (Fox & Sinha ). The authors further propose that guanfacine may be an effective medication to reduce craving and relapse vulnerability in other forms of addiction as well, because of its ability to improve cognitive and emotional control over drug‐seeking behavior (Fox & Sinha ).…”
Section: Discussionsupporting
confidence: 87%
“…Clinical data has suggested that the non-specific beta-adrenergic receptor antagonist propranolol and the alpha 2a agonist guanfacine may decrease cocaine-withdrawal induced anxiety, and lower cocaine-craving (Fox and Sinha, 2014; Fox et al, 2012, 2008; Kampman et al, 2011, 2001). Similar data was obtained in a preclinical setting in which antagonism of the beta receptors within the BNST blocks anxiety like behavior following an immobilization stressor (Cecchi et al, 2002).…”
Section: Intrinsic Composition Of the Bnstmentioning
confidence: 99%
“…Understanding the neurobiological mechanisms that underlie cue‐induced craving is critical to the development of effective treatment. It has been demonstrated that α 2 ‐AR agonists decrease cue‐induced drug craving in humans (Jobes et al ; Sinha et al ; Fox & Sinha ), pointing to a potential role of noradrenergic signaling in relapse prevention. In addition, noradrenergic signaling has been implicated in cocaine‐evoked conditioned place preference (Jasmin et al ), escalated cocaine intake by self‐administration (Zhang & Kosten ; Wee et al ), cocaine subjective effects (Newton et al ) and reinstatement of cocaine seeking (Zhang & Kosten ; Smith & Aston‐Jones ; Schroeder et al ) in rats.…”
Section: Introductionmentioning
confidence: 99%